2021
DOI: 10.1007/s11244-021-01462-9
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Paradox: The Interaction of Methanol with ZSM-5 at Room Temperature

Abstract: The adsorption of methanol in HZSM-5 at low temperatures has long been regarded as an associative process involving hydrogen bonding to the acidic zeolite hydroxyl groups. Recent studies employing inelastic neutron scattering spectroscopy (INS) have reported that complete dissociation to methoxylate the zeolite occurs at 298 K, and infrared evidence for a partial dissociation at 298 K has also been described. Here we investigate the apparent contradictions between different techniques, using a combination of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous findings stated that methanol at ambient temperatures adsorbs in the form of hydrogen-bonded species. 44 Thus, the saturation peak is explained by liquid-like CD 3 OH species in fast exchange with complexes at acid sites (CD 3 OH<>CD 3 OH@H + ). In line with this interpretation, a downfield shift of the peak maxima to 9.3 ppm is observed upon desorption of some liquid-like CD 3 OH in a vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings stated that methanol at ambient temperatures adsorbs in the form of hydrogen-bonded species. 44 Thus, the saturation peak is explained by liquid-like CD 3 OH species in fast exchange with complexes at acid sites (CD 3 OH<>CD 3 OH@H + ). In line with this interpretation, a downfield shift of the peak maxima to 9.3 ppm is observed upon desorption of some liquid-like CD 3 OH in a vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of the OH functionality in the INS spectrum was shown to be a consequence of the very strong hydrogen bonding that broadened the bands to such an extent that they disappeared into the background. 79 It was also found that methoxylation was dependent on the number of methanol molecules present in the zeolite pore. The immobility of methanol in HZSM-5 is attributed to the strong hydrogen bonding that makes the diffusion an order of magnitude slower 80 than in other zeolites e.g.…”
Section: The Three Stages Of the Catalyst's Life Inductionmentioning
confidence: 99%
“…However, the absence of the characteristic librational bands of water [28], between 400 and 600 cm − 1 , on the INS spectrum of MOR + DME + heat suggests that the reaction stops in step (1) and methanol would be hydrogen bonded to the zeolite Brønsted site. A recent study on the interaction of methanol with ZSM-5 has shown the complexity of the INS spectrum [29] and several scenarios are proposed to explain that the bands from Brønsted sites are not observed.…”
Section: In the Absence Of Comentioning
confidence: 99%